Geopolitical Challenges in Public Governance - Aslam, Mohd Mizan Mohammad; Mahadi, Syed Razak Syed; Mizan, Muhd Nabhan (Indo Consultan Energi, 2024)
Geopolitics is the study of how Earth's geography both physical and human, affects politics and international relations. The Ancient Greek terms γῆ (gê), which means